Unveiling the Meaning of Love אהב: Between Politics and Romance in the Story of David and Jonathan - Pardede, Harold (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
This study investigates the evolving interpretation of the relationship between David and Jonathan in the book of Samuel. Recent scholarship has sparked controversy by suggesting a possible homosexual connection between the two figures. This research challenges such interpretations by revisiting the concept of love (אהב) within ancient Near Eastern and biblical covenants, drawing on the foundational work of William Moran. Employing textual criticism and exegesis, the analysis focuses on the Hebrew terms חפץ and נעם used in 1 Samuel 19:1 and 2 Samuel 1:23, 26. By examining these terms alongside supporting evidence from the Hebrew Bible and ancient Aramaic texts, the study argues that these words carry primarily political connotations, signifying